Idiosyncratic Development of Receptive and Free Active Vocabulary: To what extent do essay types and receptive vocabulary contribute to the lexical richness? - YILDIZ, MUSTAFA (JET (Journal of English Teaching), 2022)
The present study seeks to explain the role of different essay types and proficiency level based on receptive vocabulary knowledge on learners’ free active vocabulary. The study includes the works done in a 15-week academic term by 26 EFL students with C1 level English proficiency. At the beginning of the research, the participants are applied Vocabulary Size Test (Nation & Beglar, 2007) to determine their receptive vocabulary knowledge and divided into two groups according to their results from VST: the more proficient group who master 8000 or more word families and the less proficient group who master less than 8000 word families. Throughout the semester, they have written two essays on each of two different essay types: comparison-contrast essay and cause-effect essay. In order to determine the participants’ free active vocabulary, two different scores, i.e., detailed Lexical Frequency Profile (Laufer and Nation, 1995) and condensed Lexical Frequency Profile (Laufer, 1995), are calculated in the writings of the participants. The results indicate that neither essay types nor proficiency based on receptive vocabulary knowledge has any significant effect on learners’ free active productive vocabulary.